Microalgae disruption techniques for product recovery: influence of cell wall composition - Alhattab, Mariam; Kermanshahi-Pour, Azadeh; Brooks, Marianne Su-Ling (Journal of applied phycology, 2019)
Microalgae are one of the most promising feedstocks for the production of commodity and value-added products. However, the use of microalgae as a feedstock is hampered by the process economics and sustainability. Overall sustainability can be improved by employing energy-efficient cell disruption and recovery processes to maximize the extraction of desired compounds from microalgal biomass. Most often, extraction processes are conducted with solvents using untreated, chemically treated, or mechanically treated cells. However, microalgal cell walls are sometimes structurally robust, complex, and chemically diverse and high energy inputs or large quantities of chemicals are required to extract products from within the cell. Various chemical, biological, and physical techniques have been employed to disrupt the cell walls from a variety of microalgae species, and these include the use of surfactants, autoclave, microwave, sonication, bead milling, enzymatic hydrolysis, high-pressure homogenization, and steam treatments. Although the cell wall structure is important for product recovery, it is often not considered when selecting the most appropriate disruption method. In this study, the cell wall structure of selected microalgae species and the effectiveness of various cell wall disruption techniques on product recovery are reviewed. It was concluded that future research must focus on developing an understanding of the relationship between cell wall disruption mechanisms and cell wall composition and structure, as well as optimizing the energy consumption of the disruption technique. This approach would enable the design of innovative cell wall disruption techniques for an enhanced product recovery.